Understanding and probable area of difficulty of tax agents towards the proposed Goods and Service Tax in Malaysia - Bidin, Zainol; Marimuthu, Munusamy; Othman, Mohd Zainudin (2014)
Malaysian Government wanted to replace the Sales and Service Tax with Goods and Service Tax (GST) by 2015. The government would only introduce once everyone understand and familiar with the tax. This study is aimed to explore the perception of tax agents towards the proposed GST.Two constructs namely understanding and probable area of difficulty were used to measure the GST perceptions. A survey was carried out to acquire the data from 1,200 tax agent throughout Malaysia. A total of 155 questionnaires were used to analyze using descriptive statistics. Test of reliability and validity were also done on the two constructs.The result indicated that tax agents in Malaysia have good understanding towards the Government intention to introduce GST.Respondents also indicated that the most prominent probable area of difficulties in GST was the understanding or knowledge of GST.All the items in the two constructs have mean score of above 3.00.Both the cronbach alpha value and KMO value have more than 0.800 for all the two constructs.The findings suggest that the attitude, awareness,understanding and preparedness of tax agents are positive towards the implementation of GST in Malaysia. This study provides important and valuable inputs for the Government to implement strategic plan to enhance the level of understanding to taxpayers so that GST can be introduced without obstacles.